Effects of spatial pattern and cultivar on weed control and grain yield in rice at reduced rates of herbicide - Hashem - Aminpanah (Bioscience Journal, 2014)
To evaluate the effects of herbicide rate, cultivar, and spatial pattern on rice grain yield and weed suppression, a field experiment was conducted on a lowland rice field at the Rice Research Station of Tonekabon, north of Iran, in 2011. The experimental design was a split plot-factorial where the whole plot portion was a randomized complete block with three replicates. Main plots were pretilachlor rates (0, 0.5, 1, 1.5, 2 L ha-1 of pretilachlor). The subplots were factorial combinations of two crop spatial patterns (uniform and wide-row planting patterns, 20Ã— 20 and 30 Ã— 13 cm, respectively) and two traditional rice cultivars ('Hashemi' and 'Deylamani'). Regardless of cultivar and spatial pattern, rice grain and biological yields, panicle number per m2, leaf area index, and herbicide efficacy increased, while weed biomass decreased with increasing pretilachlor application rate. Rice grain and biological yields, panicle number per m2, leaf area index, and herbicide efficacy were significantly greater in uniform planting pattern than in wide-row planting pattern when averaged over cultivars and pretilachlor rates. Moreover, uniform planting pattern of rice plants suppressed weeds 39% better than wide-row planting pattern as averaged across pretilchlor rates and cultivars. 'Deylamani' produced grater grain and biological yields, panicle number per m2, leaf area index than 'Hashemi' as averaged across pretilachlor rates and spatial patterns. This experiment illustrated that uniform spatial pattern increased weed suppression, herbicide efficacy, and grain yield.